2016
DOI: 10.7778/jpkm.2016.30.1.045
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Recent Trend of Chief Complaint of Korean Pediatric and Adolescent Outpatients

Abstract: The purpose of this study is to investigate about chief complaints of Korean pediatrics and adolescent outpatients in the ○○ university hospital for their recent trend. MethodsThe study was composed of 4,677 new patients aged between 1 month and 20 years who had been visited pediatrics in ○○ university hospital from 2012 January to 2015 December. Results1. Among those patients, majority was early childhood as 51.4%, followed by early childhood, late childhood, infancy, and adolescence. 2. Chief complaints in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…The experts suggested that separate questionnaires for all childhood age groups and adolescence are needed and should be developed to cover items according to the growth and development of each childhood and adolescence period. After a discussion session, the authors' decision was to develop a questionnaire for children aged 1-5 years first, which according to a survey is the most common age group of all patients in the outpatient clinics of KM pediatrics [48][49][50]. It is known that there is no clear evidence of the validity or reliability of self-reporting measures in children younger than 5 years; it is necessary to use the observational reports of parents or other caregivers and special clinical measures when assessing the health status of children in this age range [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experts suggested that separate questionnaires for all childhood age groups and adolescence are needed and should be developed to cover items according to the growth and development of each childhood and adolescence period. After a discussion session, the authors' decision was to develop a questionnaire for children aged 1-5 years first, which according to a survey is the most common age group of all patients in the outpatient clinics of KM pediatrics [48][49][50]. It is known that there is no clear evidence of the validity or reliability of self-reporting measures in children younger than 5 years; it is necessary to use the observational reports of parents or other caregivers and special clinical measures when assessing the health status of children in this age range [14].…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by the Delphi panel's additional comments, questionnaires needed to be developed individually for each age group, so the authors decided to develop a proxy-reported outcome measure for children aged 1-5 years for starters. This age group was found to be most frequent of all pediatric ages in the KM pediatric outpatient clinic [48][49][50]. The draft of the new questionnaire, based on the conceptual framework, consists of 7 domains and 44 items.…”
Section: Preliminary Conceptual Framework and Draft Of Questionnairementioning
confidence: 99%
“…The rate of ASD among the outpatients that responded was less than 5%, which might be related to the low prevalence of ASD [ 2 , 3 ]. In addition, KM may be used infrequently to treat ASD in Korea [ 30 – 32 ]. Patients with ASD treated by the respondents were predominantly aged 3–5 or 6–10 years, when multiple responses were allowed.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, a trend toward earlier onset of puberty among boys and girls has been described (Anderson et al 2003;Euling et al 2008;Eveleth 2017;Herman-Giddens et al 1997;Herman-Giddens et al 2001;Karpati et al 2002;Lee et al 2016;Paris et al 2016;Wacharasindhu 2017;Wyshak and Frisch 1982). These trends in the timing of puberty, a period of physical and psychological development, have raised concerns regarding the potential impact of environmental factors, including endocrine disrupting chemicals (EDCs) (Blakemore et al 2010;Buck Louis et al 2008;Lee and Styne 2013;Sisk and Foster 2004).…”
Section: Introductionmentioning
confidence: 98%